Load Bearing Masonry (LBM) system in a developing country - Ramli, Nor Azlinda; Abdullah, Che Sobry; Mohd Nawi, Mohd Nasrun (2014)
Load-bearing masonry is an alternative method for construction industry especially in the housing project.The adoption of the LBM brings a huge beneficial effect to construction and organization productivity.However, research in the field of the LBM system adoption is still in its limitation. The comprehensive reviews of the literature demonstrate that the majority of the research is discusses about the development and potential of the system compared with investigate the factors influence the adoption of the system.Therefore, this study aims to discuss the past research for LBM system in construction industry.